2020
DOI: 10.1259/bjr.20200206
|View full text |Cite
|
Sign up to set email alerts
|

Focal nodular marrow hyperplasia: Imaging features of 53 cases

Abstract: Objective: To describe the characteristic imaging features of focal nodular marrow hyperplasia (FNMH). Methods and materials: Retrospective review of all patients with a diagnosis of FNMH between January 2007 and September 2019. Results: The study included 53 patients, 7 males and 46 females with a mean age of 58 years (range 12–95 years). All had MRI with conventional spin echo sequences showing a poorly defined round/oval lesion with mild T1W iso/hyperintensity compared to skeletal muscle, low T2W turbo spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 31 publications
0
18
0
5
Order By: Relevance
“…It is important to note that some normal variants of bone marrow (including red marrow islands and focal nodular marrow hyperplasia), as well as some signal abnormality patterns such as bone marrow edema-like signal (usually non-neoplastic in nature), are also hypointense relative to normal bone marrow on T1w sequences [5,6]. However, because these non-bone marrow-replacing lesions usually contain fat, their SI is not quite as low as that of bone marrow-replacing lesions.…”
Section: Fluid-and Fat-sensitive Sequencesmentioning
confidence: 99%
“…It is important to note that some normal variants of bone marrow (including red marrow islands and focal nodular marrow hyperplasia), as well as some signal abnormality patterns such as bone marrow edema-like signal (usually non-neoplastic in nature), are also hypointense relative to normal bone marrow on T1w sequences [5,6]. However, because these non-bone marrow-replacing lesions usually contain fat, their SI is not quite as low as that of bone marrow-replacing lesions.…”
Section: Fluid-and Fat-sensitive Sequencesmentioning
confidence: 99%
“…Along these lines, another study found that the T2w dixon fat only images provided significantly more contrast than the standard T1w sagittal image for detecting multiple myeloma spinal lesions. 19 Nevertheless, Heynen et al 20 showed that T2w dixon sequences are less sensitive than standard T1w sequences in detecting hip and pelvic occult fractures. The T1w sequence still remains as the current gold standard sequence in identifying areas of marrow infiltration, showing lower signal compared to the surrounding skeletal muscle.…”
Section: Chemical Shift Imagingmentioning
confidence: 99%
“…The T1w sequence still remains as the current gold standard sequence in identifying areas of marrow infiltration, showing lower signal compared to the surrounding skeletal muscle. 20 Chemical shift imaging also provides a useful means for identifying areas of focal nodular marrow hyperplasia (FNMH) which can mimic a bone tumour/metastases. 20 This is especially useful in the setting of known primary malignancy where the patient presents with an 'indeterminate,' lesion.…”
Section: Chemical Shift Imagingmentioning
confidence: 99%
See 2 more Smart Citations